THE INFLUENCE OF PRODUCT QUALITY, BRAND IMAGE AND DIGITAL MARKETING ON PURCHASE INTENTION ERIGO PRODUCTS TO USERS SHOPEE APPLICATION - Sabrina Luvita; Teuku Zulkarnaen; Heriyana; Halida Bahri (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This research was conducted to find out the influence of product quality, brand image and digital marketing on buying interest in Erigo products at the Faculty of Economics and Business, Malikussaleh University. This research uses a quantitative approach where the data used is primary data collected from distributing questionnaireson line(google forms) and processed using SPSS 25.0. The sample in this study was 120 people. The data analysis technique used in this research is multiple linear regression, validity test, reliability test. The classic assumption test consists of the normality test, multicollinearity test, and heteroscedasticity test. Test the hypothesis using a partial test (t test). The research results show that product quality, brand image and igital marketing has a positive and significant effect on purchasing interest in Erigo products at the Faculty of Economics and Business, Malikussaleh University.